Testosterone plus lifestyle therapy improves skeletal muscle glycolysis in older men with obesity and hypogonadism - Viola, Viola; Aguilar, Marlene; Nava, Maria Liza Duremdes; Celli, Alessandra; Armamento-Villareal, Reina; Barnouin, Yoann; Napoli, Nicola; Putluri, Nagireeddy; Qualls, Clifford; Villareal, Dennis T. (Frontiers in Endocrinology, 2026)
ObjectiveWeight loss in older men with obesity and hypogonadism accelerates musculoskeletal decline, yet the underlying metabolic mechanisms remain unclear. Testosterone replacement therapy (TRT), when added to lifestyle therapy (LT), mitigates this decline, but its metabolic basis has not been defined. We examined skeletal muscle metabolomic adaptations to LT with or without TRT, focusing on glycolysis, the pentose phosphate pathway (PPP), the tricarboxylic acid (TCA) cycle, and carnitine metabolism to identify dominant pathways of metabolic adaptation.DesignRandomized, double-blind, placebo-controlled trial (LITROS).MethodsEighty-three men aged 65 years or older with obesity (BMI ≥30 kg/m2), hypogonadism (testosterone <10.4 nmol/L), and frailty (Physical Performance Test score ≤31) were randomized to 26 weeks of LT plus TRT (LT+TRT) or LT plus placebo (LT+Pbo). A metabolomic substudy was performed in 44 participants, who underwent serial biopsies of the vastus lateralis for targeted LC-MS/MS analysis of intermediates in glycolysis, PPP, TCA cycle, and carnitine metabolism.ResultsAmong the pathways examined, only glycolysis showed a consistent and significant response to LT+TRT versus LT+Pbo (between-group p = 0.005). This response was characterized by increases in preparatory (G6P/F6P, FBP) and payoff (3PG, 2PG, PEP) intermediates, along with higher lactate concentrations, whereas pyruvate remained stable. The PPP showed limited changes, and neither the TCA cycle nor carnitine metabolites exhibited consistent patterns. In LT+TRT, the glycolysis factor score was positively correlated with VO2peak (r=0.47, p = 0.04) and inversely correlated with triglycerides (r=–0.52, P = 0.01) and the metabolic syndrome score (r=–0.48, p = 0.02). No significant correlations were observed in LT+Pbo.ConclusionsTRT during LT selectively enhances skeletal muscle glycolysis, identifying glycolic activation as the dominant metabolic adaptation in this mechanistic study. By increasing glycolytic flux under calorie restriction, TRT may produce efficient ATP generation while conserving amino acids, supporting muscle and bone preservation and improving aerobic and cardiometabolic function in older men with obesity and hypogonadism.